Research on the Movement of Overlying Strata in Shallow Coal Seams with High Mining Heights and Ultralong Working Faces - Fu, Yuping; Li, Chuantian; He, Yongliang (Applied sciences, 2024)
To study the roof movement and ground pressure evolution characteristics of an ultralong working face in a shallow coal seam with a high mining height, the Shangwan Coal Mine in the Shendong mining area was used as the research background, and the physical and mechanical parameters of the surrounding rock were determined through rock mechanics experiments. A physical simulation model was built considering the 7 m mining height of the 12301 fully mechanized working face of the Shangwan Coal Mine to simulate and study the evolutions of the movement, fracture and collapse of the coal seam, direct roof, and basic roof and overlying strata during the mining process. The mechanical characteristics of the support, mechanism of roof collapse, and changes in the working resistance of the support were analysed and simulated. The research results indicate that when mining at a height of 7 m, the direct roof and basic roof strata collapse in layers; the basic roof strata collapse backwards, the rock block arrangement is more irregular, and the range of the basic roof that can form structural rock layers extends higher. After the basic roof rock fractures, it cannot form a masonry beam structure and can only form a cantilever beam structure. The periodic fracture of the cantilever beam causes periodic pressure on the working face. These research results are of great significance for planning the further mining of shallow coal seams with high mining heights and ultralong working faces in the Shendong mining area, as well as for improving the control of overlying strata.